طرابلس الغرب من خلال مجلس المبعوثان العثماني (1908 – 1911م) - بوصبيع إبراهيم سميرة; جديد منيا (My University, 2024)
من خلال هذه الدراسة المتواضعة تحدثنا فيها عن طرابلس الغرب كولاية عربية تابعة للدولة العثمانية خلال العهد العثماني الثاني ( 1835- 1911)، تعرفنا على الأوضاع العامة السياسية، الإدارية، الاقتصادية، الاجتماعية الدينية والثقافية، وأهم مميزات كل وضع على حدة، كما تحدثنا عن التمثيل النيابي بهذه الولاية الذي شملها على غرار الولايات الأخرى ضمن اصلاحات السلطان عبد الحميد الثاني ( 1876- 1908م)، سوف نتعرف على نصيب هذه الولاية من هذه الاصلاحات، وعلى أي مقياس كان اختيار النواب، كم عدد المقاعد الممثلة لهذه الولاية من الاصلاحات وعلى أي مقياس كان يختار النواب كم كان عدد المقاعد المتمثلة لهذه الولاية، لماذا تغير عددها بعد 1908م، ولقد تطرقنا إلى أهم القضايا التي تم تداولها في المداولات النيابية خلال مجلس المبعوثان ( 1876- 1908م). In this comprehensive analysis, we have examined Tripoli Al-Gharb as an Arab province under the governance of the Ottoman Empire in the Second Ottoman Era (1835-1911). Our investigation delved into the prevailing political, administrative, economic, social, religious, and cultural landscapes, meticulously dissecting the distinctive characteristics of each aspect. Furthermore, we scrutinized the framework of parliamentary representation within this region, a component of the Sultan Abdul Hamid II's reforms (1876-1908). Our forthcoming focus will encompass an exploration of this province's stake in the reform initiatives, the criteria guiding the selection of representatives, the allocation of parliamentary seats, the methodology behind representative appointments, and the rationale underpinning alterations in seat allocation post-1908. We have touched on the most important issues that were discussed in parliamentary deliberations during the Council of Envoys (1876-1908 AD)
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: طرابلس الغرب; Tripoli Ouest; Tripoli West